University education, conflicts, borders and cooperation: interdisciplinary perspectives between Brazil and Ukraine - Holod , Andrii; Alves , Fábio Lopes; Ilina , Mariia; Felenchak , Yuliia; Ghizzi, Hevelyn Priciely (Educere et Educare, 2024)
The dossier "University education, conflicts, borders and cooperation: interdisciplinary perspectives between Brazil and Ukraine" brings together national and international articles that problematize the complex relations of higher education in conditions of crisis, cross-border cooperation between cultures and fields of knowledge. With interdisciplinarity as a horizon, the manuscripts discuss how universities can build bridges across disciplinary boundaries in order to promote peaceful coexistence in regions marked by conflict and division. The texts address the potential of internationalization and university cooperation. Overall, this issue provides a thought-provoking and timely contribution to debates on the role of higher education in building more just and peaceful societies.